1990
DOI: 10.1177/019459989010200605
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Postoperative Bleeding Incidence between General and Local Anesthesia Tonsillectomies

Abstract: Postoperative bleeding after tonsillectomy is a problem that has earned the respect and cautious attention of the most experienced surgeons. The incidence of postoperative hemorrhage after tonsillectomy, as well as many factors affecting this incidence, has been extensively investigated. A possible factor that has not been well studied as a possible influence in postoperative tonsillectomy bleeding is the choice of anesthetic. A study was completed comparing the incidence of postoperative tonsillectomy bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
0
9
0
4
Order By: Relevance
“…Because of the small number of patients in the latter group, the incidence of PTH in the two groups cannot be compared in our study. In the literature, the incidence of PTH for tonsillectomy under local anesthesia is higher than for tonsillectomy under general anesthesia [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the small number of patients in the latter group, the incidence of PTH in the two groups cannot be compared in our study. In the literature, the incidence of PTH for tonsillectomy under local anesthesia is higher than for tonsillectomy under general anesthesia [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the study reported the experiences of 2 surgeons (430 total procedures): the first used an 8-mg preoperative intravenous dexamethasone dose, injected 5 ml of 1% lidocaine with 1:100,000 epinephrine into the peritonsillar space before making the incision, and packed the fossae with oxymetazoline-soaked tonsil sponges after tonsil removal; the second surgeon used no intravenous dexamethasone and no injected or topical vasoconstrictors. In their discussion, the authors quote data from a study by Kennedy and Strom [57] demonstrating a threefold increase in bleeding in patients who were injected with epinephrine before tonsillectomy (12.5%) versus control patients who were not injected (1.4%). A follow-up study by Blatt [58] reported that the bleeding rate after local tonsillectomy was only 1% when lidocaine 1% is used without epinephrine.…”
Section: Other Studies Demonstrating Increased Risk Of Hemorrhagementioning
confidence: 99%
“…14 However, proponents of the technique state that it is a much faster procedure with minimal intraoperative blood loss and negligible incidence of immediate post-tonsillectomy hemorrhage. 15 Most have found no difference between the two methods, but prefer diathermy because of the decreased operating time needed and drier field that was come to a similar conclusion. 16 Our results were similar to previous studies that have not shown the chronic infection is a risk factor for post-tonsillectomy hemorrhage.…”
Section: Discussionmentioning
confidence: 95%